Impact of nitrogen topdressing on the performance of wheat yield and grain protein - Horváth, Csaba; Kassai, Katalin M.; Nyárai, Ferenc H.; Szentpétery, Zsolt; Tarnawa, Ákos (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2015)
Yield samples of winter wheat Triticum aestivum L. varieties taken from the Nagygombos experimental site of the Szent István University in two different crop years have been evaluated. Impact of N topdressing on the performance of yield and protein was studied. In case of five high quality wheat varieties yield and protein values were examined. The results suggest that ascending doses of N topdressing, and split applications had a beneficial effect on the yield figures, the amount of protein content as well as the total protein yield of the wheat varieties examined.
Keywords: yield; grain protein; total protein yield; winter wheat